Pengaruh Metode Ibrah Mauidzah Terhadap Kecerdasan Spritual dan Aktivitas Belajar Siswa pada Mata Pelajaran Qur’an Hadist di MTsN 1 Agam - Abu Hasdi; Charles Charles; Salmi Wati; Afrinaldi Afrinaldi; Andy Riski Pratama (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Education plays an important role in the development of human resources, promoting social capabilities, and the development of individuals linking them to society and the environment. Islamic education, in particular, aims to instil spiritual and ethical values and develop learners' scientific knowledge.  This study explored the effect of the Ibrah Mauidzah Qur'anic Storytelling Method on students' spiritual intelligence and learning activities at MTsN 1 Agam. The correlational quantitative research method was used to test the research hypothesis. the type of research used is correlational. It is a study that looks for the relationship between the independent variable and the dependent variable with a sample of 35 students obtained using the accental sampling technique. The results of the analysis show that the Ibrah Mauidzah Method has a significant effect on increasing students' spiritual intelligence and learning activities. The tcount values for spiritual intelligence and learning activity were 3.076 and 3.779 respectively, both greater than the ttable of 2.034, with a p-value <0.05. These findings indicate that the method is effective in improving understanding and appreciation of religious values, as well as increasing student engagement in the learning process. This research confirms the importance of integrating moral and spiritual approaches in education to achieve a balance of students' intellectual and spiritual development.